National stroke management plan in Uruguay: Challenges and opportunities - Amorín, Ignacio; Savia, Adolfo; Gaye, Andres; Camejo, Claudia; Triviño, Brayan; Muñoz, Matías; Yancev, Sebastian; Menendez, Tamara; Decima, Rodrigo (Frontiers in Neurology, 2023)
Stroke accounts for 5.5% of the national Global Burden of Disease (GBD) and approximately 2000 deaths per year in Uruguay. In order to respond to this disease, the Ministry of Public Health (MPH) of Uruguay devised the National Stroke Plan (NSP). Scientific associations, universities, scholars and patient organizations, both at national and international level, took part in devising it. This ends with the generation of the national stroke management guidelines, including a bundle of measures based on the best evidence available, which were accompanied by presidential regulatory decrees and several ordinances that set the foundations of the legal framework for their implementation as of 2020. Forty-two (42) Stroke Ready Centers (SRC) and seven (7) Comprehensive Stroke Centers (CSC) were strategically established and linked to ensure compliance with international accessibility recommendations, offering, in turn, the required training for their health care teams. A prehospital care protocol was also created for all countrywide mobile units. For NSP assessment, stroke was included as a “Care Goal (objective)” for the whole Health System, providing the involved health care organizations with a financial incentive for compliance with the basic objectives related to the treatment of hyperacute stroke. The NSP started operating during the COVID-19 pandemic and, considering the special circumstances imposed, it made it possible to maintain hyperacute medical care and increase population access to recanalization treatment, particularly mechanical thrombectomy. The purpose of this article is to share our experience in the development of the NSP by describing some preliminary outcomes.